Diverse molecular phenotypes of ATP7B protein in Wilson disease: functional insights and therapeutic implications - Mukherjee, Shashwata (Environmental and Experimental Biology, 2022)
Wilson disease is a rare genetic disease causing copper accumulation due to mutations in the copper transporter protein ATP7B gene. Its varied clinical features result from toxic build-up of the ion primarily in liver and brain. The large number and variety of ATP7B mutations and influence of modifiers are suggested to account for only part of this heterogeneity. Exciting research on functional aspects is gradually elucidating the interesting behaviour of mutant ATP7B under different physiological conditions. Subtle perturbations in its delicate architecture have been shown to affect diverse functional properties of this copper pump. It is possible that compound heterozygotes bearing mutations with two different molecular phenotypes may partially complement each other’s defect, giving rise to unpredictable clinical presentation. These have tremendous potential in contributing to the clinical variability. More recent findings indicate the role of interacting partners in modulating the disease phenotype. The present review aims to outline the major strategies for in vitro evaluation of mutant ATP7B protein function, summarize the information on such studies in the literature, and gain new insights on the molecular behaviour and regulation of the protein. The functional consequence of mutations at 86 residue positions was reviewed through search in Pubmed and this information was analysed. A glimpse on studies at the transcription level is also provided. The development of new generation drugs to correct the underlying molecular defect is briefly discussed to emphasize how basic research to elucidate the molecular phenotype can have the potential to usher in the age of precision medicine for this disease.